Development of Community Empowerment Models in the Sub-Urban Area as an Effort to Improve HIV/AIDS Knowledge - Setyaningsih, Eka; Nugroho, Efa (JHE (Journal of Health Education), 2020)
Background: The case of HIV/AIDS is a global problem that must be addressed immediately. A total of 6,176 cases of HIV/AIDS in Indonesia occurred in the age group 20-49 years. One of the causes of the high incidence of HIV/AIDS is the lack of knowledge about HIV/AIDS as a preliminary study found that 63.2% of teenagers in Mluweh Village did not know about HIV/AIDS. This study aims to determine the model of community empowerment to increase knowledge of HIV/AIDS of adolescents in Mluweh Village. Methods: This study used an intervention method. The informant in this study is adolescents Mluweh Village. The technique of taking data using interviews then data analyzed descriptively. Results: Adolescents in Mluweh Village did not have comprehensive information on HIV/AIDS, which was due to low levels of education, still considered a taboo of reproductive health education, and lack of information resources on HIV/AIDS. Teenagers feel the need to do the formation of the Working Group (Pokja) of HIV/AIDS as an effort to increase knowledge of HIV/AIDS. The formation of the Working Group (Pokja) on HIV/AIDS should also be accompanied by the organizational structure and work program. Conclusion: The formation of the HIV/AIDS Working Group (Pokja) by utilizing local potentials is very necessary as an effort to increase adolescent knowledge about HIV/AIDS.